The life and times of Takabuti in ancient Egypt : investigating the Belfast mummy - David, A. Rosalie; David, A. Rosalie; Murphy, Eileen M.; Murphy, Eileen M. (Liverpool scholarship online, 2021)
The mummy of Takabuti is one of the best known antiquities in the Ulster Museum, Belfast. Takabuti was a young woman who lived in Egypt during a tumultuous period, c. 600 BC. Her mummy was unwrapped and investigated in Belfast in 1835. While the focus of the book is on Takabuti, it shows how the combination of archaeological, historical and inscriptional evidence with multidisciplinary scientific techniques can enable researchers to gain a wealth of information about ancient Egypt. This not only relates to the individual historical context, ancestry and life events associated with Takabuti, but also to wider issues of health and disease patterns, lifestyle, diet, and religious and funerary customs in ancient Egypt